Pengembangan Kurikulum Pendidikan Kewarganegaraan dalam Kampus Merdeka Berdasar Optimalisasi Kompetensi Kewarganegaraan serta Pelayanan Berkualitas terhadap Mahasiswa - Nanggala, Agil (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
This research was conducted to provide argumentative information that Citizenship Education is able to collaborate with the independent campus policy, so that it has a positive impact on efforts to manage the nation's demographic bonus, through the development of the Citizenship Education Law on an independent campus, which leads to scientific efforts to optimize citizenship competencies and provide quality services for students. , in order to be a strategic step in realizing Indonesian civil society. This research was carried out through a qualitative approach with a literature study method, of course the data analysis in this study focused on: data reduction, data display and drawing conclusions. The results of the study are: 1) Citizenship Education curriculum development in an independent campus is a scientific effort in optimizing student citizenship competencies, namely: civic knowledge, civic skills and civic disposition, as social capital to realize civilized citizens (civic virtue), in the context of quality services. for students, of course based on the Among Ki Hajar Dewantara system, because it focuses on practical education that guides and serves, so that students develop optimally, 2) Citizenship Education curriculum development in an independent campus uses the Tyler model, because it focuses on curriculum orientation, so that the implementation and evaluation of the curriculum can be returned to each institution. Because the substance of the Citizenship Education curriculum development in an independent campus does not limit the innovation and learning characteristics of Citizenship Education at each institution, but becomes a national indicator, so that there is harmonization of the management of the demographic bonus.